Non-motor Adverse Effects Avoided by Directional Stimulation in Parkinson's Disease: A Case Report - Alonso-Frech, Fernando; Fernandez-Garcia, Carla; Gómez-Mayordomo, Victor; Monje, Mariana H. G.; Delgado-Suarez, Celia; Villanueva-Iza, Clara; Catalan-Alonso, Maria Jose (Frontiers in Neurology, 2022)
Deep brain stimulation (DBS) is widely used for treatment of advanced, medication-refractory Parkinson’s disease. However, a significant proportion of patients may suffer adverse effects; up to 10% will present one or more transient or permanent neurobehavioral events. PATIENT AND METHODS In our case study, a 44-year-old woman diagnosed with Parkinson’s disease six years previously who was suffering from motor fluctuations, dyskinesia and freezing of gait episodes was submitted for DBS and implanted with directional electrodes. Intraoperative local field potentials (LFP) were recorded. After surgery, conventional monopolar revision was performed. Preoperative 3T MRI studies and postoperative 3D and X-ray data were integrated using the Guide DTI software application (Brainlab), and diffusion tensor imaging tractography traced from cortical areas to each subthalamic nucleus (STN) using Elements software (Brainlab). RESULTS We observed that left STN stimulation in the ring mode significantly improved motor symptoms, but the patient presented uncontrollable mirthful laughter. Stimulation was then switched to the directional mode; laughter remained when using the more posteriomedial contact (3-C+) but not 2-C+ or 4-C+ at the same parameters. Interestingly, LFP recordings showed the highest beta-band activity over contacts 4 and 2, and very scarce beta power over contact 3. The orientation of the directional leads was selected based on 3D postoperative X-rays. Associative fibers showed the shortest distance to contact number 3. CONCLUSION Stimulation of the STN can affect motor and associative loops. Use of directional electrodes is a good option to avoid not only undesirable capsular or lemniscal effects, but also limbic/associative events. Oscillatory activity in the beta range, which preferentially takes place over the somatomotor STN region and is closely related to motor improvement, provides a reliable guide for optimizing DBS programming. The importance of the exact location of electrical stimulation to determine non-motor symptoms such as mood, apathy, attention and memory, as well as the usefulness of biological markers such as LFP for optimal programming, are discussed in relation to this case.